2012
DOI: 10.1002/jbm.a.34486
|View full text |Cite
|
Sign up to set email alerts
|

Local effect of IL‐4 delivery on polyethylene particle induced osteolysis in the murine calvarium

Abstract: Wear particles generated with use of total joint replacements incite a chronic macrophage-mediated inflammatory reaction, which leads to implant failure. Macrophage activation may be polarized into two states, with an M1 proinflammatory state dominating an alternatively activated M2 anti-inflammatory state. We hypothesized that IL-4, an activator of M2 macrophages, could modulate polyethylene (PE) particle-induced osteolysis in an experimental murine model. Four animal groups included (a) calvarial saline inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 51 publications
2
64
0
Order By: Relevance
“…As previously described, 6 each of the calvaria was placed into a well of a 12-well plate and cultured with 2 mL Dulbecco's Modified Eagle's Medium (DMEM; Thermo Fisher Scientific, Waltham, MA, USA) for 24 hours at 37°C with 5% CO 2 . The culture medium was collected and stored at −20°C for assay of receptor activator of nuclear factor (NF)-κB ligand (RANKL), osteoprotegerin (OPG), TNF-α, IL-6, IL-4 and IL-10.…”
Section: Calvaria Culturementioning
confidence: 99%
See 2 more Smart Citations
“…As previously described, 6 each of the calvaria was placed into a well of a 12-well plate and cultured with 2 mL Dulbecco's Modified Eagle's Medium (DMEM; Thermo Fisher Scientific, Waltham, MA, USA) for 24 hours at 37°C with 5% CO 2 . The culture medium was collected and stored at −20°C for assay of receptor activator of nuclear factor (NF)-κB ligand (RANKL), osteoprotegerin (OPG), TNF-α, IL-6, IL-4 and IL-10.…”
Section: Calvaria Culturementioning
confidence: 99%
“…The concept of macrophage polarization was recently considered to play a role in the pathological mechanism of aseptic loosening. 1,6,7 M1 proinflammatory macrophages were activated in response to wear debris dominating the M2 antiinflammatory response. M1 macrophages secrete primarily proinflammatory cytokines such as TNF-α, IL-6 and IL-1β, while M2 macrophages produce anti-inflammatory mediators such as IL-4, IL-10 and IL-13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, anti-inflammatory cytokines and their combinations can be loaded on thin adhesive coatings. For example, local immunomodulation using well recognized antiinflammatory factor IL4 alleviated biomaterial-induced osteolysis in mice [21]. Controlled release of IL4 from polyelectrolyte multilayer-based coatings and silk biomaterials was shown to promote differentiation of macrophages with anti-inflammatory M2 properties [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches applied the antiinflammatory cytokine IL-4 alone or in combination with IL-13 to the site of particle addition [55]. Addition of IL-4 at the time of addition of particles in a subcutaneous model showed that bone thickness was improved and that TNF and RANKL expression was decreased [35]. In addition, the type of macrophage localized at the site of particle deposition was shifted to an M2 profile from an M1 profile.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%